PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA FLIPCHART TERHADAP MOTIVASI BELAJAR SISWA PADA MATERI KERAGAMAN BUDAYA DAN KEARIFAN LOKAL KELAS IV SD - Meilia br Hutapea, Chika; Darwis, Umar; Fitrah Dwi, Dara; Mujib, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the Problem Based Learning (PBL) model assisted by flipchart media on students' learning motivation in the subject matter of cultural diversity and local wisdom in Grade IV of elementary school. This study employed a quantitative research method with a Pre-experimental Design in the form of a One-Group Pretest-Posttest Design, involving 16 Grade IV students as research subjects. Data were collected using observation sheets and questionnaires that had been validated by experts. Statistical data analysis was performed using the two-tailed Paired Sample t-test. The results of the study showed that the learning observation sheet yielded an average percentage score of 92.86%, which falls under the very good category. Furthermore, the student learning motivation observation sheets revealed that, across all three meetings, the overall average motivation of Grade IV students at MIS Ulfa Khairuna indicated that 5 students, or 31%, were in the very good category, and 11 students, or 69% of the 16 students studied, were in the good category. Hypothesis testing in this study was conducted using the two-tailed Paired Sample t-test, with data processing performed using IBM SPSS Statistics Version 24. Based on the statistical test results using the two-tailed Paired Sample t-test, the Sig. (2-tailed) value obtained was 0.000 < 0.025. Therefore, it can be concluded that H₀ is rejected and Hₐ is accepted, meaning that there is a significant effect of the Problem Based Learning (PBL) Model assisted by Flipchart Media on Students' Learning Motivation in the Subject of Cultural Diversity and Local Wisdom in Grade IV of Elementary School.